2018
DOI: 10.17221/726/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the glomalins content in the soil under winter wheat in different crop production systems

Abstract: The aim of the study was to evaluate the glomalins content (total glomalin (TG), easily extractable glomalin (EEG) and glomalin-related soil proteins (GRSP)) in the soil under winter wheat from different crop production systems. The experiment involved four different cultivation systems: organic, integrated (INT), conventional (CON), monoculture-conventional (MON). The highest content of TG and GRSP proteins were observed in organic system. A strong positive correlation was observed between the total number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In accordance with the results observed in this work, the CM at the highest water regimes (L96 and L68) is similar in wheat grown under different management systems, under temperate climate condition (Galazka et al, 2018) and is also within the average observed (41%) in a study that evaluated CM in 94 wheat genotypes (Lehnert et al, 2017).…”
Section: Occurrence and Distribution Of Arbuscular Mycorrhizal Fungi Speciessupporting
confidence: 91%
“…In accordance with the results observed in this work, the CM at the highest water regimes (L96 and L68) is similar in wheat grown under different management systems, under temperate climate condition (Galazka et al, 2018) and is also within the average observed (41%) in a study that evaluated CM in 94 wheat genotypes (Lehnert et al, 2017).…”
Section: Occurrence and Distribution Of Arbuscular Mycorrhizal Fungi Speciessupporting
confidence: 91%
“…These results suggest that GRRP is more directly related to soil GRSP and mediates SOC stock by influencing GRSP storage in the soil. Indeed, an increase of SOC with increasing GRSP and the contribution of GRSP to SOC dynamics are well documented (Anna et al, 2018; Singh, Rai, et al, 2017; Singh, Zhu, et al, 2020). Furthermore, our multivariate analysis demonstrated a better interconnection among these measured variables by projecting them in a two‐dimensional plane derived from the two most higher‐ranked PCA components (Figure 6).…”
Section: Discussionmentioning
confidence: 97%
“…In ecological systems, there are also observed well organized fungi communities (Wittwer et al 2018). The research on the glomalin content of the soil, which is glycoproteins produced by arbuscular mycorrhizal (AM) fungi, has shown a higher content of these proteins in soils from organic farming compared to soils from conventional and integrated systems, and also from winter wheat monocultures (Gałązka et al 2018). This indicates a higher activity of AM fungi in these soils.…”
Section: Organic Farming and Microorganismsmentioning
confidence: 99%